2020 Global Stocktaking of National Accounts Statistics : Availability for Policy and Surveillance - Silungwe, Anthony; Baer, Andrew; Guerreiro, Vanda (Washington, D.C. : International Monetary Fund, 2022)
This paper analyzes the availability, methodological soundness, and scope of National Accounts statistics in IMF member and non-member countries in 2020. National Account statistics are instrumental in the development of fiscal and monetary policy and in monitoring economic developments. This analysis examines the appropriateness of the current set of global national accounts statistics for current policy development and highlights regions where further development may be required. The assessment is based on the results of a national accounts survey conducted by Fund staff that examined the scope of national accounts programs in IMF member countries. The survey was completed by statistical authorities between March 2021 and July 2021. The information reflects the state of National Accounts Programs as of the end 2020. In cases of non-response, IMF staff used information taken from the IMF's Dissemination Standards Bulletin Board (DSBB) and country websites to provide the status of national accounts compilation practices. This analysis summarizes the following key indicators: time lag of national accounts benchmarks, availability annual and quarterly GDP estimates, vintage of the System of National Accounts (SNA), index formula used for calculating annual constant price (volume) estimates, availability of GDP by different approaches, timeliness of disseminating and annual and quarterly GDP estimates, availability institutional sector accounts, and access to source data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Benchmarking and GDP; Environmental Accounts; Institutional Sectors and National Accounts; Measurement and Data on National Income; Product Accounts and Wealth; South Africa